Resumes vs. application forms: Why the stubborn reliance on resumes? - Risavy, Stephen D.; Robie, Chet; Fisher, Peter A.; Rasheed, Sabah (Frontiers in Psychology, 2022)
The focus of this Perspective article is on the comparison of two of the most popular initial applicant screening methods: resumes and application forms. The viewpoint offered is that application forms are superior to resumes during the initial applicant screening stage of selection. This viewpoint is supported in part based on criterion-related validity evidence that favors application forms over resumes. For example, the biographical data (biodata) inventory, which can contain similar questions to those used in application forms, is one of the most valid predictors of job performance (if empirically keyed), whereas job experience and years of education, which are often inferred from resumes and cover letters, are two of the least valid predictors of job performance (among commonly used screening criteria). In addition to validity evidence, making decisions based on application forms as opposed to resumes is likely to help organizations defend against claims of discriminatory hiring while enhancing their ability to hire in a more diverse, equitable, and inclusive manner. For example, applicant names on resumes can lead to screening bias against members of identifiable subgroups, whereas an applicant’s name can be easily and automatically hidden from decision-makers when reviewing application forms (particularly digital application forms). Despite these convincing arguments focused on applicant quality and diversity, a substantial research–practice gap regarding the use of resumes and cover letters remains.